2019
DOI: 10.7554/elife.48828
|View full text |Cite|
|
Sign up to set email alerts
|

Function of hTim8a in complex IV assembly in neuronal cells provides insight into pathomechanism underlying Mohr-Tranebjærg syndrome

Abstract: Human Tim8a and Tim8b are members of an intermembrane space chaperone network, known as the small TIM family. Mutations in TIMM8A cause a neurodegenerative disease, Mohr-Tranebjærg syndrome (MTS), which is characterised by sensorineural hearing loss, dystonia and blindness. Nothing is known about the function of hTim8a in neuronal cells or how mutation of this protein leads to a neurodegenerative disease. We show that hTim8a is required for the assembly of Complex IV in neurons, which is mediated through a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 72 publications
4
62
0
Order By: Relevance
“…Firstly, we excluded changes in the abundance of SFXN proteins due to alterations in gene expression by measuring mRNA abundance for SFXN1, SFXN2, SFXN3 and MTHFD2. Expression of SFXN1, SFXN2 and SFXN3 was unchanged in AGKKO HEK293 cells and Tim9MUT HEK293 cells (Kang et al, 2019) (Figure 2A). Tim9 also functions in the TIM22 pathway (Kang et al, 2019), suggesting the observed changes to the SFXN proteins were indeed posttranslational.…”
Section: Sideroflexins Are Novel Substrates Of the Tim22 Complexmentioning
confidence: 97%
See 2 more Smart Citations
“…Firstly, we excluded changes in the abundance of SFXN proteins due to alterations in gene expression by measuring mRNA abundance for SFXN1, SFXN2, SFXN3 and MTHFD2. Expression of SFXN1, SFXN2 and SFXN3 was unchanged in AGKKO HEK293 cells and Tim9MUT HEK293 cells (Kang et al, 2019) (Figure 2A). Tim9 also functions in the TIM22 pathway (Kang et al, 2019), suggesting the observed changes to the SFXN proteins were indeed posttranslational.…”
Section: Sideroflexins Are Novel Substrates Of the Tim22 Complexmentioning
confidence: 97%
“…Expression of SFXN1, SFXN2 and SFXN3 was unchanged in AGKKO HEK293 cells and Tim9MUT HEK293 cells (Kang et al, 2019) (Figure 2A). Tim9 also functions in the TIM22 pathway (Kang et al, 2019), suggesting the observed changes to the SFXN proteins were indeed posttranslational. Protein levels of SFXN1 and SFXN4 were reduced in AGKKO HEK293 and Tim9MUT HEK293 mitochondria, as confirmed by western blot (Figure 2B).…”
Section: Sideroflexins Are Novel Substrates Of the Tim22 Complexmentioning
confidence: 97%
See 1 more Smart Citation
“…For label free quantitative LC-MS/MS experiments of mitochondria, statistical analysis of data was consistent with published analyses from our and other groups employing similar instrumentation and methods (46,62,63). All experiments were performed in at least 3 independent biological replicates.…”
Section: Experimental Design and Statistical Rationalementioning
confidence: 74%
“…Tris-tricine SDS-PAGE was performed as previously described (44)(45)(46)(47). Samples for electrophoresis were combined with SDS-PAGE loading dye (50 mM Tris-Cl (pH 8.…”
Section: Gel Electrophoresis and Immunoblot Analysismentioning
confidence: 99%